Plasma lipid profile and leptin concentration in super-obese children - Hendarto, Aryono; Nasar, Sri Sudaryati; Sjarif, Damayanti Rusli (Paediatrica Indonesiana, 2007)
Background Leptin induced weight loss is completely specific for adipose tissue loss, whereas food restriction result in both loss of adipose tissue and lean body mass in mammals. Most obese person has high endogenous leptin levels, indicating leptin resistance. There has been lack of data regarding plasma leptin level in Indonesian obese children. Objective This study was aimed to investigate the plasma leptin level and lipid profile in super-obese children. Methods This was a cross sectional study performed in Pediatric Out Patient Clinic Mangunkusumo Hospital and Private Women & Children Hospital in Eastern part of Jakarta. Super-obese is defined as children with BMI above 97 centiles CDC 2000 chart. Blood sample was obtained from all subjects, consisted of peripheral blood picture, lipid profiles and leptin level. Results Seventy nine super-obese children were eligible with age ranged between 12 months and 180 months and mean of age was 84.9 months (SD 36.8). More than 60% subjects had high LDL cholesterol, while 19% had low HDL level. The lowest leptin blood level was 2.877 Î¼ g/dL, while the highest was 70.430 Î¼ g/dL (mean 23.990; SD 12.726). Forty five subjects, all boys, had increased plasma leptin level. Conclusions In super-obese children, most of the subject experienced hyperlipidemia (LDL cholesterol) followed by hypertriglyceridemia. There was small number of low HDL cholesterol found. Super-obese girls had normal serum leptin level, in contrast, more than 60% super-obese boys had elevated serum leptin level.